Variability in soybean yield responses to elevated atmospheric CO2 Insights from non-structural carbohydrate remobilisation during seed filling - Xu, Ying (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.